Pronunciation of Ghayeni Plural Nouns with a Final Consonant Within Stratal Optimality Theory - Bashir Jam; Zohreh Sadat Naseri; Parya Razmdideh (زبان پژوهی, 2022)
The most common plural markers in Persian are /-hɑ/ and /-ɑn/. The former is mostly used in speech and the latter is more common in writing (MacKenzie, 1961, p. 50; Rokhzadi, 2011, p. 128). It has different forms in some Persian dialects influenced by phonetic factors. This research aims at investigating the plural marker in Ghayeni Persian within Stratal Optimality Theory (SOT) (Kiparsky, 1998a, 2000). In SOT, there are (at least) two layers. The order of the constraints between the layers can be different, which predicts the opaque relation between the input and the final output. In SOT, the output of each layer enters the next layer as the input along with the special affixes of that layer (if any), and this process continues until the final output is produced.  In Ghayeni Persian, which is spoken in the city of Ghayen in the province of South Khorasan, the suffix /-hɑ/ is not used at all, and the plural /-ɑn/ is present only in the phonological representation. None of the plural markers of standard Persian are observed in the Pronunciation of Ghayeni plural nouns. If the plural form of a word is expressed alone or the followed word or morpheme begins with a consonant, the consonant /n/ in the plural morpheme is deleted. The plural /n/ is not deleted in some cases. In this study, the phonological behavior of the plural marker is examined in words that end in consonant. The previous researches that have studied the plural marker in Persian have not examined the pronunciation of the plural from this point of view.